2018
DOI: 10.1002/ecm.1290
|View full text |Cite
|
Sign up to set email alerts
|

Biodiverse cities: the nursery industry, homeowners, and neighborhood differences drive urban tree composition

Abstract: Abstract. In arid and semiarid regions, where few if any trees are native, city trees are largely human planted. Societal factors such as resident preferences for tree traits, nursery offerings, and neighborhood characteristics are potentially key drivers of urban tree community composition and diversity, however, they remain critically understudied. We investigated patterns of urban tree structure in residential neighborhoods of the Salt Lake Valley, Utah, combining biological variables, such as neighborhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 52 publications
(104 reference statements)
5
125
0
1
Order By: Relevance
“…In this regard, a majority of trees in the southwestern U.S. urban areas were shown to be non‐native (Nowak , Avolio et al. ) because the original vegetation prior to urbanization was predominantly shrubland. Pincetl et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a majority of trees in the southwestern U.S. urban areas were shown to be non‐native (Nowak , Avolio et al. ) because the original vegetation prior to urbanization was predominantly shrubland. Pincetl et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Avolio et al. ; Table ). It has been suggested that traits related to overall plant size, such as plant height and larger growth forms (usually perennial), can influence aesthetic preferences.…”
Section: Methodsmentioning
confidence: 96%
“…The valley was originally mainly composed of shrublands and is now dominated by non-native vegetation in cultivated landscapes (Avolio, Pataki, Trammell, & Endter-Wada, 2018), resulting in a substantial alteration in vegetation composition and structure that has to be sustained with irrigation. Despite receiving one of the lowest annual rainfall rates in the country, Utah uses the most water per capita in the United States as end-user consumption, and 60% of residential water is used outdoors (DWR, 2015).…”
Section: Study Locationmentioning
confidence: 99%
“…Previous urban ecology studies that test the hypothesis of ecological homogenization have used Jaccard's index (McKinney 2006), Sørensen's index (Pearse et al 2018 (Yang et al 2017, Avolio et al 2018, and a variety of qualitative methods, as well as specifically designed protocols which have included data on herbaceous vegetation and soils (Groffman et al 2014). Our study, which further incorporated disparate data sources, demonstrates that the Raup-Crick dissimilarity indices, based on presence/absence data, are robust to sampling differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional multivariate analysis methods, such as MANOVA, make stringent assumptions which are untenable for most ecological datasets (McArdle and Anderson 2001). More recently, permutational analysis of variance (PERMANOVA; Anderson 2001) has been used to compare urban forests composition across geographic and urbanization gradients (Blood et al 2016, Yang et al 2017, as well as to test for differences among neighborhood species compositions within an urban region (Avolio et al 2018). Thus, non-parametric methods are preferable.…”
Section: Community Composition Comparisonsmentioning
confidence: 99%